1984
DOI: 10.1300/j013v09n04_02
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Problems of Sexual Assault Survivors

Abstract: Attempts to downplay the sexual component of sexual assault may actually result in an injustice to sexual assault survivors as it may desensitize professionals working with sexual assault survivors to the possible development of sexual problems. Of 371 sexual assault survivors evaluated, more than 40% reported that they were experiencing sexual problems as a result of their assaults. In addition, these assault-related sexual problems can be chronic, enduring for many years. The need to screen for and provide t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
6

Year Published

1988
1988
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(34 citation statements)
references
References 8 publications
1
27
0
6
Order By: Relevance
“…However, much of this body of research that reports CSA survivors engage in increased levels of sexual behavior is drawn from samples of young adult women such as college students (Alexander & Lupfer, 1987;Meston, Heiman, & Trapnell, 1999). There is another body of studies documenting that CSA survivors have an increased likelihood of experiencing sexual avoidance and dysfunctions which primarily comes from studies with clinical samples (Becker et al, 1984;Jehu, 1988;Sarwer & Durlak, 1996;Westerlund, 1992). CSA survivors in the clinical samples were usually older than the women in studies examining college-age women.…”
Section: Discussionmentioning
confidence: 99%
“…However, much of this body of research that reports CSA survivors engage in increased levels of sexual behavior is drawn from samples of young adult women such as college students (Alexander & Lupfer, 1987;Meston, Heiman, & Trapnell, 1999). There is another body of studies documenting that CSA survivors have an increased likelihood of experiencing sexual avoidance and dysfunctions which primarily comes from studies with clinical samples (Becker et al, 1984;Jehu, 1988;Sarwer & Durlak, 1996;Westerlund, 1992). CSA survivors in the clinical samples were usually older than the women in studies examining college-age women.…”
Section: Discussionmentioning
confidence: 99%
“…In these studies, the majority of women have reported at least some perceived growth (Cole & Lynn, 2010), blamed themselves only mildly (Glenn & Byers, 2009), and were less likely than survivors of other sexual crimes (i.e., incest and both incest and rape) to experience sexual problems (Becker, Skinner, Abel, Axelrod, & Cichon, 1984).…”
Section: Outcomes For Rape Survivorsmentioning
confidence: 99%
“…Certains auteurs affirment que certaines victimes ont peur de la sexualité (Gorcey et al, 1986 ;Becker et al, 1984 ;Briere et Runtz,1987), alors que d'autres développent un dégoût, une aversion, de l'anxiété ou encore de la culpabilité à son sujet (Bagley et MacDonald, 1984;Jehu, 1989 ;Herman et al, 1986 ;Russell, 1986).…”
Section: La Sexualisation Traumatisanteunclassified
“…Par conséquence, les femmes victimes d'abus étant enfants ressentent peu de désir et manifestent des dysfonctions sur le plan du désir et de l'excitabilité (Becker et al, 1984 ;Tsai, 1979). À l'autre extrémité de la balance, certaines victimes adoptent un comportement de promiscuité : elles changent souvent de partenaires sexuels (Tsai et al, 1979) ou elles vivent une sexualité compulsive (Meiselman, 1978 ;Herman, 1981 ;Courtois, 1979) allant jusqu'à la prostitution (Earls et David, 1990 ;James et Mayerling, 1979 ;Silbert et Pines, 1981, cités par Finkelhor, 1986.…”
Section: La Sexualisation Traumatisanteunclassified